Stage Specific Life Table of Invasive Pest Mealybug, Phenacoccus Solenopsis (Tinsley) Under Cotton Field Conditions - Sahito, Hakim Ali; Kousar, Tasneem; Mangrio, Wali Muhammad; Mallah, Nisar Ahmed; Jatoi, Faheem Ahmed; Shah, Zafar Hussain; Kubar, Waheed Ali (Current Research in Agricultural Sciences, 2017)
The field study was conducted on at the experimental field of SALU – Khairpur during, 2016. Two hundred eggs were kept for each replication on cotton plants grown in large pots. When eggs hatched, the life table parameters such as; apparent mortality, survival fraction, mortality survivor ratio, indispensable mortality and k-value were studied. Natural enemies such as; Chrysoperla carneae, lady bird beetles, Spiders and Anasius bambawallae were found active on the potted and surrounding cotton plants in the field conditions. The total mortality in egg stage went to 19.00%. The mortality percentages of 1st instars due to natural enemies recorded was (18.73%) while, in 2nd instars (13.13%) mortality was recorded. The total combined mortality in 1st and 2nd instars was recorded (26.34%) and (15.64%), respectively. However, the mortality of 3rd instars and pupae due to parasitoids were recorded (7.28%) with the total mortality (10.26%) and the total mortality (54.83%) in cotton potted plants was recorded. Consequently, (45.17%) of adults survived with male and female ratio as ♂1:6.52♀, respectively. The highest apparent mortality was (26.34%), indispensable mortality (96.89) and k-value (0.13) recorded in 1st instar. The maximum survival fraction was recorded (0.90) in third instars/pupae with the total k-value generations (0.35). The study revealed that the predators and parasitoids should be encouraged in cotton field when mealybugs appear, because predators are highly voracious feeder of 1st and 2nd instars whereas; the parasitoid, A. bambawallae is known as main controlling natural enemy of cotton mealybug.